Cobalt Nanoparticles Confined in Carbon Cages Derived from Zeolitic Imidazolate Frameworks as Efficient Oxygen Electrocatalysts for Zinc‐Air Batteries. Issue 4 (29th January 2019) - Chen, Xuncai; Yu, Zixun; Wei, Li; Yuan, Ziwen; Sui, Xiao; Wang, Yanqing; Huang, Qianwei; Liao, Xiaozhou; Chen, Yuan
Abstract: Rechargeable zinc (Zn)‐air batteries are a potential solution to effectively incorporate electricity generated from renewable energy sources into our daily consumption, which requires electrocatalysts to catalyze the oxygen‐reduction reaction (ORR) and the oxygen evolution reaction (OER) on the air electrode. Here, we report a high‐performance bifunctional oxygen electrocatalyst by confining cobalt (Co) nanoparticles in nitrogen (N)‐doped porous carbon cages derived from a metal‐organic framework, i. e., ZIF‐8. Co precursors were first impregnated into ZIF‐8 by a double solvent method. Afterward, carbonization produces highly dispersed Co nanoparticles (with the average diameter of 6.2 nm) confined in N (11.4 at.%) doped porous carbon cages (434.5 m 2 g −1 ). This electrocatalyst exhibits excellent catalytic activity for both ORR and OER with long‐term stability. It delivers a half‐wave potential of 0.838 V vs. reversible hydrogen electrode, an electron transfer number of 3.9 for ORR, an overpotential of 0.411 V at 10 mA cm −2, and a Tafel slope of 71.2 mV dec −1 for OER. Rechargeable Zn‐air batteries assembled using this electrocatalyst demonstrate an open‐circuit potential of 1.48 V, a specific capacity of 731.1 mAh g −1, and good rechargeability. The simple and efficient method can confine metal nanoparticles in porous carbon cages, which can be further explored to synthesize novel electrocatalysts for various energy conversion applications. Abstract : Locking cobalt nanoparticles in porous carbon cages : nitrogen‐doped porous carbon cages derived from metal‐organic frameworks confine cobalt nanoparticles, limiting aggregation and leaching during electrochemical oxygen reactions. The hybrid material exhibits good catalytic activity and long‐term stability for the oxygen reduction and evolution reactions, suitable for application as bifunctional electrocatalysts in high‐performance rechargeable zinc‐air batteries.